Studi Literatur: Faktor yang Mempengaruhi Kinerja Keuangan UMKM - Fitri Nadia Salsabila Souseii (Prosiding, 2026)
The development of Micro, Small, and Medium Enterprises (MSMEs) in Indonesia has a significant contribution to the national economy. However, many MSMEs still face financial performance challenges due to limited financial knowledge and management. This study aims to examine the factors that affect the financial performance of MSMEs. The literature review approach is used as the method in this article. Data sources were obtained through secondary data by reviewing 15 articles obtained from the Google Scholar database that have been selected based on three criteria. The results show that financial literacy, financial management, human resource competency, and access to capital are factors that have a significant influence on the financial performance of MSMEs. Financial literacy is the most dominant factor in improving the financial performance of MSMEs because it forms the basis for financial decision-making. Financial management also plays an important role in ensuring financial sustainability. Meanwhile, HR competency and access to capital complement each other in supporting the growth of MSMEs.